Ellipsis in Comparatives. - Lechner, Winfried (Studies in Generative Grammar SGG., 2004)
Generative analyses of comparatives traditionally include two construction specific ellipsis operations, Comparative Deletion and Comparative Ellipsis. Drawing from a wide array of new data, the present monograph develops a novel, directly semantically in.